Equine bullous pemphigoid - Case report - Fontes, Thanielle Novaes; de Farias, Soraya Santos; Machado, Gessica Aline Cruz; Mascarenhas, Mariana Bezerra; da Silva, Adriana Lopes; Brandão, Estela Batista; Nogueira, Vivian de Assunção; Peixoto, Tiago da Cunha (Brazilian Journal of Veterinary Medicine, 2017)
ABSTRACT. Fontes T.N., de Farias S.S., Machado G.A.C., Mascarenhas M.B., da Silva A.L., Brandão E.B., Nogueira V.A. & Peixoto T.C. [Equine bullous pemphigoid - Case report.] Penfigóide bolhoso em equino - Relato de caso. Revista Brasileira de Medicina Veterinária, 38(Supl.1):55-59, 2016. Departamento de Anatomia, Patologia e Clínicas Veterinárias, Escola de Medicina Veterinária e Zootecnia, Universidade Federal da Bahia, Av. Adhemar de Barros, 500, Ondina, Salvador, BA 40170-110, Brasil. E-mail: tcpeixoto@ufba.br Bullous pemphigoid is a rare and severe autoimmune dermatosis caused by the production of autoantibodies. It has been reported in humans, dogs, cats and pigs, but, in horses, it has recently been reported in the USA. In Brazil, there were no references of the disease in horses. Due to the rarity of the disease and variety of differential diagnoses, the aim of this study was to register the first occurrence of the disease in equine in Brazil, and to describe the clinic-pathological and histopathological aspects. The horse was treated at the Veterinary Medicine Hospital of UFBA, presenting chronic skin lesions. On physical examination, there were multiple erythematous, ulcerated, crusty and itchy lesions at head, medial thigh and ventral thoracic region. Therapeutic attempts based on topical antiseptics, antibiotics and antifungals were ineffective. Parasitic, fungal and bacterial diseases have been ruled out by additional tests. Due to the worsening of clinical symptoms, the owner opted for euthanasia. At necropsy, there were macular, erosive, ulcerative lesion and intense vesicular-pustular in the muco-cutaneous junctions (lips, nostrils and anus) and coronary band. The oral mucosa was found to be hyperemic, eroded and ulcerated, with rare intact vesicles / blisters, especially the gums located close to the upper teeth and lower incisors, the inner surface of the lips and cheeks and hard palate and oral cavity floor. Throughout the dorsal surface of the tongue, there were large ulcers, usually, coalescing. Histopathology of the skin and oral mucosa revealed several sub-epidermal blistering. The diagnosis of bullous pemphigoid was based on clinical and epidemiological data, the macroscopic findings and confirmed by histopathology.